Which studies test whether self-enhancement is pancultural? Reply to Sedikides, Gaertner, and Vevea, 2007 - Heine, S.; Kitayama, S.; Hamamura, Takeshi (Blackwell Publishing Limited, 2007)
What types of studies test the question of pancultural self-enhancement? Sedikides, Gaertner, and Vevea (2007) have identified inclusion criteria that largely limit the question to studies of the better-than-average effect (i.e. 27 out of 29 effects that they include as ‘validated’ and ‘relevant’). In contrast, other effects which they labelled as ‘unvalidated’ or ‘irrelevant’ used methods other than the better-than-average effect (i.e. 24 out of 24 effects). Because Sedikides et al. are drawing conclusions about pancultural self-enhancement and not the pancultural better-than-average effect, these excluded studies are relevant to the hypothesis under question. Ignoring the findings from other methods is highly problematic, in particular because these other methods yield results that conflict with those from the better-than-average effect. An analysis of effects from all studies reveals no support for pancultural self-enhancement.